Persepsi Wisatawan Terhadap Kawasan Suci Pura Masceti Di Desa Medahan Kecamatan Blahbatuh Kabupaten Gianyar - Gede Surya Arta Darma; I Putu Anom (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2018)
The Sacred area of ??Masceti Temple is located in Medahan Village, Blahbatuh District. The Number of tourists began increasing is an indication of the tourism potential that can be developed. This is the background of choosing the topic